Experimental investigation of concrete-filled steel tubular longitudinal gusset plate connections. (September 2016) - Xu, Fei; Chen, Ju; Jin, Wei-liang
Abstract: A series of tests on the concrete-filled tubular gusset plate T–connections is presented in this paper. Three different loading conditions, including axial tension, eccentric tension and in-plane bending, were applied to the brace. The chord wall slenderness ratio ( D / t ) of the test specimens ranged from 48 to 75. The material properties of the steel and concrete used in the test specimens were measured. Each connection was tested to failure, and the behavior under loading was recorded. Punching shear failure of the chord member was the main failure mode observed during the tests. The test results were compared with the current AISC-360 and CIDECT DG1 design predictions, which only concern hollow section steel tubular connections. It is shown that the design strengths predicted by the current design rules are quite conservative for all the test specimens examined in this study. It is recommended that the contribution of concrete be considered in the design because it could effectively restrain the deformation of the chord wall that was observed in the test. The proposed design equations predict the ultimate strengths of the concrete-filled tubular gusset plate T–connections generally well. Highlights: Experiment has been conducted on concrete-filled steel tubular longitudinal gusset plate connections. Three different loading conditions, including axial tension, eccentric tension and in-plane bending, were applied to the brace. Chord deformation, failure mode and ultimate strength of test specimens were obtained. Design method for strength prediction was proposed with the consideration of concrete filled in the chord.